Trust and distrust within foreign-invested firms in transition economies : the case of China. - Ong, Poh Hoon. (2008)
This paper attempts to address the gaps in Lewicki et al.’s [1998] work which conceptualizes the co-existence of trust and distrust. The objective of this paper is to consolidate the varying views of trust and distrust issues from past literatures, and subsequently develop a model on the interaction of trust antecedents that lead to the conditions of different levels of trust and distrust. To facilitate the application of the issues in trust and distrust, the paper discusses trust antecedents in the context of China.